2018
DOI: 10.3390/polym10070767
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Devulcanized Crumb Rubbers in Polypropylene Based Thermoplastic Dynamic Vulcanizates

Abstract: Because of the chemically crosslinked 3D molecular structure of rubbers, their recycling is a challenging task, especially when cost efficiency is also considered. One of the most straightforward procedures is the grinding of discarded rubber products with subsequent devulcanization. The devulcanized rubber can be used as a feedstock for fresh rubber compounds or can be blended with uncured virgin rubber and thermoplastic polymers to form thermoplastic dynamic vulcanizates (TDVs). TDVs combine the beneficial (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Moreover, authors indicated unsatisfactory compatibility and adhesion between HDPE and microwave treated GTR (regardless of extrusion parameter), what limit potential application of prepared blends. Simon et al [66] investigated polypropylene based thermoplastic dynamic vulcanizates obtained by twinscrew extrusion. At first they prepared materials containing model rubber comprising in 70% of SBR and in 30% of NR, which was then replaced partially (10, 20 and 30 wt%) by microwave-treated crumb rubber.…”
Section: Gtr+25 B160/220 -Mwmentioning
confidence: 99%
“…Moreover, authors indicated unsatisfactory compatibility and adhesion between HDPE and microwave treated GTR (regardless of extrusion parameter), what limit potential application of prepared blends. Simon et al [66] investigated polypropylene based thermoplastic dynamic vulcanizates obtained by twinscrew extrusion. At first they prepared materials containing model rubber comprising in 70% of SBR and in 30% of NR, which was then replaced partially (10, 20 and 30 wt%) by microwave-treated crumb rubber.…”
Section: Gtr+25 B160/220 -Mwmentioning
confidence: 99%
“…With the increasing requirements for environment protection and resource saving, thermoplastic vulcanizates (TPVs) have attracted more attention because of their good processability and easy recyclability . The effective way to prepare TPVs is through dynamical vulcanization, which is the process of cross‐linking an elastomer during its melt mixing with a molten plastic under dynamic condition . A significant number of TPVs are produced through this method, such as polylactide (PLA)/natural rubber (NR), PLA/epoxidized natural rubber (ENR), PLA/nitrile butadiene rubber (NBR), poly(vinylidene fluoride) (PVDF)/acrylic rubber (ACM), ethylene‐propylene‐diene monomer (EPDM)/polypropylene (PP), PVDF/ENR, polyamide 12 (PA12)/hydrogenated acrylonitrile butadiene rubber (HNBR), and ethylene octene copolymer (EOC)/poly dimethyl siloxane (PDMS) rubber …”
Section: Introductionmentioning
confidence: 99%
“…6,7 The effective way to prepare TPVs is through dynamical vulcanization, [8][9][10] which is the process of cross-linking an elastomer during its melt mixing with a molten plastic under dynamic condition. 11,12 A significant number of TPVs are produced through this method, such as polylactide (PLA)/natural rubber (NR), 13,14 PLA/epoxidized natural rubber (ENR), [15][16][17] PLA/nitrile butadiene rubber (NBR), 18 poly(vinylidene fluoride) (PVDF)/acrylic rubber (ACM), 19 ethylene-propylene-diene monomer (EPDM)/polypropylene (PP), [20][21][22][23] PVDF/ENR, 24 polyamide 12 (PA12)/hydrogenated acrylonitrile butadiene rubber (HNBR), 25 and ethylene octene copolymer (EOC)/poly dimethyl siloxane (PDMS) rubber. 26 The properties of TPVs strongly depended on the final morphology, which were affected by many factors, such as the cross-linking degree of the rubber phase, composition, viscosity and elasticity of individual components, preparation method, and processing condition.…”
Section: Introductionmentioning
confidence: 99%
“…Among the most-studied methods, the ultrasound method uses ultrasound waves to produce cavitation in the rubber, which generates tensions that are able to break the chemical bonds [3,5,[11][12][13][14][15][16][17][18]. Another de-vulcanization method based on the action of microwaves presents some advantages that make it one of the most promising for the recycling of rubber [2][3][4]13,15,[18][19][20][21][22], including its physical nature, the volumetric heating of the material by the microwaves, and the possibility of high productivity [23].The aging of elastomers can be defined as the degradation process produced by the interaction between a material and an environment, modifying their structure and properties (i.e., mechanical, electrical, chemical, and/or thermal). It is a complex chemical process that occurs under the influence of heat, oxygen, light, ozone, and mechanical tension, and it results in time-dependent modifications of the chemical and physical properties [24].…”
mentioning
confidence: 99%